The Role Of Health Department Of Blora Regency In The Implementation Of Bpjs Based On Act No. 40 Of 2004 On The National Social Security System To Improve Health Service To The Society - Denny Kusuma; Widayati Widayati; Siti Rodhiyah Dwi Istinah (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The regional government through the Health Department became the backbone of the implementation of the national strategic program, including JKN-KIS program. In various legislations such a role that includes licensing, facilitator, as well as giving recommendations and the availability of health facilities and the organization of health services for the implementation of the Health Insurance program. This study aims to determine the Role of Health Department of Blora Regency in the Implementation of BPJS Based On Act No. 40 of 2004 on National Social Security System to improve health services to the society and the obstacles that arise and solutions. The method used is the juridical sociological, descriptive analytical research specifications. The data used are primary data and secondary data, so that the method of collecting data through field studies and literature. Data analysis method used is qualitative analysis. As the blade is used the analysis of role theory and the theory of legal certainty. The results showed that the Role of Health Department of Blora Regency in the Implementation of BPJS Based On Act No. 40 of 2004 on National Social Security System to improve service to the public is as regulators, implementers and donors. The obstacles that arise in the implementation of BPJS in Blora is the increased fees but then disconnected MA which no increasing fees, any health facilities which can not service BPJS members because still not accredited the solution is that facilities apply a new accreditation to KARS, the role of Health Department in the implementation of BPJS not maximum so the solution is make a new regulation for empowerment the role of Health Department as regulator.Keywords: Health Department; BPJS; National Social Security System; Health Services.